2017
DOI: 10.1002/jnr.24197
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of feeder‐free human induced pluripotent stem cell–derived cortical neuron progenitors in adult male Wistar rats with focal brain ischemia

Abstract: The use of human induced pluripotent stem cells (hiPSCs) eliminates the ethical issues associated with fetal or embryonic materials, thus allowing progress in cell therapy research for ischemic stroke. Strict regulation of cell therapy development requires the xeno-free condition to eliminate clinical complications. Maintenance of hiPSCs with feeder-free condition presents a higher degree of spontaneous differentiation in comparison with conventional cultures. Therefore, feeder-free derivation might be not ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…In the present study, ep-iPSC-NPC-transplanted animals showed a gradual improvement in their functional deficit during the 11 weeks after transplantation, especially in rotarod, mNSS, and stepping tests. Some studies have used iPSC-NPCs transplanted during the acute phase of stroke [19,21], and other studies found a functional recovery in stroke animals transplanted with iPSCs-NPCs in the subacute phase of stroke (1 week after stroke induction) [15,20,24]. In the present study, ep-iPSC-NPC transplantation in the subacute phase of stroke restored functional defi-cits in stroke animals.…”
Section: Stem Cells Internationalsupporting
confidence: 67%
See 4 more Smart Citations
“…In the present study, ep-iPSC-NPC-transplanted animals showed a gradual improvement in their functional deficit during the 11 weeks after transplantation, especially in rotarod, mNSS, and stepping tests. Some studies have used iPSC-NPCs transplanted during the acute phase of stroke [19,21], and other studies found a functional recovery in stroke animals transplanted with iPSCs-NPCs in the subacute phase of stroke (1 week after stroke induction) [15,20,24]. In the present study, ep-iPSC-NPC transplantation in the subacute phase of stroke restored functional defi-cits in stroke animals.…”
Section: Stem Cells Internationalsupporting
confidence: 67%
“…Previous studies have shown that the engraftment and differential potential of transplanted ESCor iPSC-derived NPCs were highly variable. Approximately 5~30% of cells survive 4 weeks after transplantation, with the numbers of engrafted cells gradually decreasing thereafter [15,[17][18][19][20][33][34][35][36]. Even if the cells had survived, the number of differentiated neurons among the grafted cells was low in this study (less than 10% of engrafted cells).…”
Section: Stem Cells Internationalmentioning
confidence: 54%
See 3 more Smart Citations